Conservation Agriculture for Sustainable Intensification (CASI) in Eastern India - CGIAR Research Program on Wheat (2020)
Policy brief by ICAR, CIMMYT & partners lays out clear case to policy-makers about the benefits of CASI plus a road map for accelerating its adoption in Eastern India.